IbM TENUN AQILA DAN LUMINTU - Musyafa Musyafa; Hadi Ismanto (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2018)
Troso's weaving product as a heritage of Troso village ancestors has so far spread and expand rapidly to all parts of Indonesia and become one of the economic support of Jepara society in general and society of Troso village in particular. However, with the strategic role, there are still obstacles in its empowerment. As the problems faced by both partners are UMKM Aqila Weaving and UMKMLumintu. Devotion to the implementation of science and technology for this community wants to overcome the problems faced by both partners are aspects of management, production, and marketing.The solutions offered are as follows: 1). Preparation of administrative system, 2). Added non-machine loom (ATBM) with anchors, and 3). Providing online marketing facilities. The method of implementation is done by stages of administration and productivity improvement. With the expertise and expertise of the implementing team, this community service will succeed